Concepción de Familia Construida Desde La Narrativa De Un Grupo de Niños Entre Seis y Once Años Hijos de Padres en Situaciones de Conflicto Familiar (2014)
The purpose of this research is to describe the narratives associated with concept of family, of boys and girls in situations of family conflict. For its realization based on contributions from authors such as Hernández, Ritvo, Gergen, Epston, Dallos, among others researchers. A qualitative methodological framework was implemented, using as resources collection and analysis of children's stories. 5 participants were interviewed among the 6 and 11 years old, who attend the Psychological Care Center of the Antonio University Nariño, requesting psychological advice. The stories are then analyzed. contrasting them with the theoretical resources you have on the concept of family.